1995
DOI: 10.1002/ijc.2910640402
|View full text |Cite
|
Sign up to set email alerts
|

Detection of TP53 gene mutation in human meningiomas: A study using immunohistochemistry, polymerase chain reaction/single‐strand conformation polymorphism and dna sequencing techniques on paraffin‐embedded samples

Abstract: Mutations in the TP53 tumor suppressor gene have been studied in different types of brain tumors. Little is known about this genetic event in human meningioma, a mostly benign tumor. To investigate the frequency of TP53 gene mutations in human tumors derived from meningeal tissues, paraffin-embedded tissues from 30 cases (including 2 malignant and 4 atypical meningiomas, as well as 2 hemangioblastomas and 3 hemangiopericytomas) were screened by immunohistochemistry. Polymerase chain reaction/single strand conf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
31
1

Year Published

1996
1996
2014
2014

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(36 citation statements)
references
References 31 publications
4
31
1
Order By: Relevance
“…Absence of TP53 gene mutations in meningiomas has also been reported by Ohgaki et al (54) and single meningiomas with TP53 mutation have been found by other authors (55). Unless there are mutations in the rarely affected regions of TP53, alterations of this gene appear to be of minor significance in meningiomas.…”
Section: Discussionsupporting
confidence: 62%
“…Absence of TP53 gene mutations in meningiomas has also been reported by Ohgaki et al (54) and single meningiomas with TP53 mutation have been found by other authors (55). Unless there are mutations in the rarely affected regions of TP53, alterations of this gene appear to be of minor significance in meningiomas.…”
Section: Discussionsupporting
confidence: 62%
“…33 TP53 mutations or deletions were reported in atypical and anaplastic meningiomas, with a frequency ranging from 0% to 62%; however, grade I meningioma was not affected. 4,10,27,52,55 Nevertheless, there is considerable variability among the different studies. Amatya et al 4 did not find any mutation of TP53, despite a high frequency of p53 protein expression, thus suggesting that p53 protein is wild type.…”
Section: P53mentioning
confidence: 97%
“…Although the function of p53 is still not well understood, many lines of evidence indicate that meningiomas have low levels of p53, leading to speculations that p53 mutations may be involved in the etiology of these tumors. [54][55][56] It has been demonstrated that wildtype p53 promotes degradation of HIF-1a 57 so it may be expected that inactivation of p53 either results from somatic mutations or from functional inactivation, which would lead to increased HIF-1a expression in meningiomas. If functional p53 is lost, the proapoptotic effect of HIF-1a is lost and tumor progression is stimulated by HIF-1a via induction of angiogenesis.…”
Section: Present Studymentioning
confidence: 99%